2002
DOI: 10.1002/cyto.10049.abs
|View full text |Cite
|
Sign up to set email alerts
|

Influence of EDTA and heparin on lipopolysaccharide binding and cell activation, evaluated at single‐cell level in whole blood

Abstract: Background: The use of whole blood (WB) in studying lipopolysaccharide (LPS)-induced cellular activation preserves the milieu in which LPS-cell interaction occurs in vivo. However, little information is available on using such a system at a single-cell level. We evaluated LPS binding and cell activation in WB by using flow cytometry. The influence of heparin or EDTA as anticoagulants was also addressed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 4 publications
0
10
0
Order By: Relevance
“…The test was performed as described above. Previous studies in our lab showed that anti-CD14 monoclonal antibody (clone MP9) binding to CD14 molecules on the monocyte surface was not influenced by the presence of LPS, even at concentrations of as high as 50,000 ng/ml (8).…”
Section: Methodsmentioning
confidence: 73%
“…The test was performed as described above. Previous studies in our lab showed that anti-CD14 monoclonal antibody (clone MP9) binding to CD14 molecules on the monocyte surface was not influenced by the presence of LPS, even at concentrations of as high as 50,000 ng/ml (8).…”
Section: Methodsmentioning
confidence: 73%
“…Blood samples (10 ml) were taken by venous puncture with heparin as the anticoagulant. Heparin was chosen over EDTA since EDTA can interfere with cell activation (Brunialti et al ., ).…”
Section: Methodsmentioning
confidence: 94%
“…For ex vivo TLR stimulation experiments, all blood samples were collected in Vacutainers containing the anticoagulant EDTA, as previous studies have demonstrated that the presence of heparin contributes to augmented monocyte responses to LPS via the activity of heparin-binding protein (10,19). For phagocytosis and oxidative-burst assays, blood samples were collected in Vacutainers containing the anticoagulant heparin to prevent the inhibitory effects of EDTA on these functions (4).…”
Section: Blood Collectionmentioning
confidence: 99%